Rancang Bangun Sistem Informasi Penjualan dan Pemesanan Roti Berbasis Web pada Queen Bakery Purwodadi - Maulana Nor Rohman; Sugiyamta Sugiyamta (Journal of Management and Bussines (JOMB), 2024)
This research aims to develop a web-based sales and ordering information system using the waterfall method. Xampp is used as a server, MySQL as a database, and the PHP programming language is supported by the Codeigniter framework. The resulting system is designed to increase communication efficiency and expand promotional reach. The use of black box testing is carried out to verify system functions and ensure that its performance meets expectations. The test results show that the system is running well. By implementing this web-based sales and ordering system, it is hoped that Queen Bakery can make transactions easier, reach more consumers, and provide more complete product information. The conclusion is that the integration of technology in the sales process can be an effective solution to overcome challenges in the world of the bakery business. Keywords: Information System, Waterfall, Website